Feedback from human posterior parietal cortex enables visuospatial category representations as early as primary visual cortex. Issue 1 (18th December 2017) - Li, Yanyan; Hu, Xiaopeng; Yu, Yongqiang; Zhao, Ke; Saalmann, Yuri B.; Wang, Liang
Abstract: Introduction: Categorization is a fundamental cognitive process, whereby the brain assigns meaning to sensory stimuli. Previous studies have found category representations in prefrontal cortex and posterior parietal cortex (PPC). However, these higher‐order areas lack the fine‐scale spatial representations of early sensory areas, and it remains unclear what mechanisms enable flexible categorization based on fine‐scale features. Methods: In this study, we decoded functional MRI signals and measured causal influences, across visual, parietal, and prefrontal cortex from participants performing categorization based on coarse‐ or fine‐scale spatial information in thirteen healthy adults. Results: We show that category information based on coarse discriminations was represented in the PPC, in the intraparietal sulcus region, IPS1/2, at an early stage of categorization trials, whereas representations of category information based on fine‐scale discriminations formed later during interactions between IPS1/2 and primary visual cortex (V1). Specifically, when fine‐scale discriminations were necessary, we decoded significant category information from V1 at an intermediate stage of trials and again from IPS1/2 at a late stage. IPS1/2 feedback was critical, because categorization performance improved as causal influence from IPS1/2 to V1 increased. Further, these mechanisms were plastic, as the selectivity of IPS1/2 and V1 responses shifted markedly with retraining to categorize the same stimuli into two new groups. Conclusions: Our findings suggest that reentrant processing between the PPC and visual cortex enables flexible abstraction of category information. Abstract : Posterior parietal cortex (PPC) is represented category information based on coarse spatial discriminations. When categorization required fine‐scale discriminations, PPC feedback recruited primary visual cortex (V1), where category information emerged later during the categorization process. The stronger the feedback from PPC to V1, the better the categorization performance. These findings suggest that category information emerges as early as V1 when fine‐scale discriminations are needed.